Mammographic breast glandularity in Malaysian women: data derived from radiography - Jamal, Noriah; Ng, Kwan Hoong; McLean, Donald; Looi, Lai Meng; Moosa, Fatimah (American Roentgen Ray Society (ARRS), 2004)
OBJECTIVE. This study was undertaken to estimate mammographic breast glandularity in Malaysian women from radiographic data.